Identification of myocardial injury using perioperative troponin surveillance in major noncardiac surgery and net benefit over the Revised Cardiac Risk Index. (January 2022) - Chew, Michelle S.; Puelacher, Christian; Patel, Akshaykumar; Hammarskjöld, Fredrik; Lyckner, Sara; Kollind, Malin; Jawad, Monir; Andersson, Ulrika; Fredrikson, Mats; Sperber, Jesper; Johnsson, Patrik; Elander, Louise; et al.
Abstract: Background: Patients with perioperative myocardial injury are at risk of death and major adverse cardiovascular and cerebrovascular events (MACCE). The primary aim of this study was to determine optimal thresholds of preoperative and perioperative changes in high-sensitivity cardiac troponin T (hs-cTnT) to predict MACCE and mortality. Methods: Prospective, observational, cohort study in patients ≥50 yr of age undergoing elective major noncardiac surgery at seven hospitals in Sweden. The exposures were hs-cTnT measured before and days 0–3 after surgery. Two previously published thresholds for myocardial injury and two thresholds identified using receiver operating characteristic analyses were evaluated using multivariable logistic regression models and externally validated. The weighted comparison net benefit method was applied to determine the additional value of hs-cTnT thresholds when compared with the Revised Cardiac Risk Index (RCRI). The primary outcome was a composite of 30-day all-cause mortality and MACCE. Results: We included 1291 patients between April 2017 and December 2020. The primary outcome occurred in 124 patients (9.6%). Perioperative increase in hs-cTnT ≥14 ng L −1 above preoperative values provided statistically optimal model performance and was associated with the highest risk for the primary outcome (adjusted odds ratio 2.9, 95% confidence interval 1.8–4.7). Validation in an independent, external cohort confirmed these findings. A net benefit over RCRI was demonstrated across a range of clinical thresholds. Conclusions: Perioperative increases in hsTnT ≥14 ng L −1 above baseline values identifies acute perioperative myocardial injury and provides a net prognostic benefit when added to RCRI for the identification of patients at high risk of death and MACCE. Clinical trial registration: NCT03436238 .